ANALISIS KINERJA MODULASI RADIO MICROWAVE PADA AUTOMATIC MODULATION RADIO - Hasad, Andi; Bakri, M. Amin; Hakim, Firman L. (JREC (Journal of Electrical and Electronics), 2013)
The purpose of this research was to determine the performance characteristics through modulation 16QAM modulation and 32QAM based on the range and bandwidth capacity. This research provides benefits to users microwave radio systemsandwill discussabout themodulation16 QAMand 32QAMin automaticmodulation radioforreceivepower levels, transmit powerand large of bandwidth. Analysis oftheliteraturewill be doneby displayingrelatedmaterialsthat have beendone by theprevious academic, as well asthetesting andfield observationstoobtainrealdatafrom the linkusing16QAMand32QAMmodulation